Beyond Procedural Correctness: Legal Formalism and the Search for Justice in Indonesian Criminal Law - Luthfia Rahmadani; Wahidin Wahidin (Rule of Law Studies Journal, 2025)
Abstrak Background: Indonesian criminal law enforcement frequently privileges procedural accuracy as the clearest sign of justice. Yet decisions that satisfy formal requirements may still be experienced as unfair when they disregard social context and the substance of harm. Aims: This article explores how a procedure-centered mindset narrows the meaning of justice in Indonesian criminal law and considers how restorative justice can help broaden justice beyond a strictly formal reading of legality. Methods: The study uses normative legal research with a conceptual and analytical design. Statutory provisions, doctrinal reasoning, and key scholarly debates are examined through close legal interpretation and critical assessment to map the effects of formalism and to situate restorative justice as a justice-oriented framework. Result: The analysis indicates that an overreliance on procedural correctness can turn criminal law into an exercise in compliance, where legality is treated as an endpoint rather than a means to achieve fairness. In this setting, the interests of victims, offenders, and communities risk being handled in a fragmented way, because the process is valued more than the repair of harm. Read as a framework rather than a mere policy tool, restorative justice offers a way to reconnect accountability with relationships, context, and proportional outcomes. Conclusion: The article argues that justice in Indonesian criminal law cannot be exhausted by procedural validity alone. A more adequate approach requires interpretation that is attentive to social realities, with restorative justice functioning as a conceptual bridge toward substantive justice.